081 The use of a cycle ergometer to calculate myocardial perfusion reserve with k-t SENSE-accelerated myocardial perfusion MR imaging at 3.0 Tesla. (22nd September 2015) - Lockie, T P E; Ishida, M; De Silva, K; Williams, R; Redwood, S; Marber, M; Nagel, E; Plein, S
Abstract : Background: Exercise induced stress testing is important to determine the physiological reserve of the myocardium. High heart rate (HR) and respiratory motion represent a challenge for CMR perfusion imaging requiring very fast data acquisition to minimise artefacts. Purpose: To quantify perfusion at rest and exercise-induced stress in volunteers using k-space and time sensitivity encoding (k-t SENSE) CMR perfusion at 3.0 Tesla. Methods: CMR: k-t SENSE accelerated perfusion CMR was performed on a 3T Philips Achieva® system using 0.025 mmol/kg/min Gd-DO3A-butrol and the following pulse sequence: saturation recovery gradient echo, repetition time/echo time 3.0 ms/1.0 ms, flip angle 15°, 5×k-t SENSE acceleration, 11 interleaved training profiles, WET pre-pulse (angles 120°, 90°, 180°, 140°); delay 100 ms, spatial resolution 1.8×1.8×10 mm 3, three slices at each RR interval, 40 dynamic images. For blood pool saturation correction MR images with diluted Gd-DO3A-butrol injection (0.0025 mmol/kg) were also acquired. Subjects: Eight volunteers (age 21–35 years) with no history of cardiac disease. Exercise protocol: A specially adapted supine cycle ergometer was used and attached to the sliding table inside the CMR scanner such that the subject could exercise without leaving the table and scanning could occur almost immediately after peak exercise. A standardised exercise protocol was used with increments of 20 W each minute for 6 min at a rate of 60 rpm. Rate pressure product (RPP) calculated as peak systolic blood pressure x peak HR was recorded at peak exercise. Analysis: The mid-slice was used in each subject for further analysis. After correcting for saturation of the blood signal, arterial input and myocardial output time-intensity curves were analysed with a Patlak plot method to quantify global myocardial K1 at rest and stress. Then, absolute global myocardial blood flow (MBF) at rest and stress and myocardial perfusion reserve (MPR) were calculated from the K1 measurement using the extraction fraction (EF) of the Gd contrast agent, where EF=0.5 at rest, EF=0.3 at stress. Results: All subjects successfully completed the exercise protocol. Respiratory motion artefacts were seen in all studies, but did not affect further analysis. Resting MBF value was 89.8±10 ml/min/100 g compared to stress of 302.3±141.1 ml/min/100 g (p<0.008), giving an MPR of 3.3±1.4, consistent with physiological values. RPP was 17 556±1209 indicating equivalent workload across all subjects. See abstract 081 table 1 for full data. Conclusions: k-t SENSE can be used to acquire perfusion CMR data during ergometer stress and to determine global myocardial perfusion reserve in healthy volunteers through absolute quantification of flow. More studies are required to determine regional flow distribution but this technique holds potential for the functional assessment of patients with cardiac disease.